Influence of orientation and roughness of heater surface on critical heat flux and pool boiling heat transfer coefficient of nanofluid. (September 2017) - Dadjoo, Mina; Etesami, Nasrin; Esfahany, Mohsen Nasr
Graphical abstract: Highlights: Pool boiling of silica nanofluid over an inclined surface was investigated. Heater orientation has a dramatic effect on pool boiling of nanofluid. Effect of initial roughness of surface on characteristics of boiling was studied. Boiling heat transfer was enhanced over a nanocoated surface. Abstract: Pool boiling of SiO2 /water nanofluid over a copper flat plate heater at various inclinations of the heater surface was investigated experimentally. In this work, the effect of heater surface orientation on changes in surface roughness and on the characteristics of nanofluid boiling was studied. We examined pool boiling of silica nanofluid at various concentrations (<0.1 vol.%) and various heater orientations from a horizontal state (0°) to a vertical state (90°). The results showed that in nanofluid boiling, increasing the inclination angle of the heater surface from 0° to 90° increases the critical heat flux (CHF) and decreases the boiling heat transfer coefficient (BHTC), while in boiling DI water, both for CHF and BHTC, decreases with the angle of the heater surface. Atomic force microscope images from the heater surface which has been boiled in nanofluids illustrated that surface roughness varies with the orientation of the surface. It was found that deposition of nanoparticles and bubble movements have important effects on nanofluid boiling over inclined surface. In addition, the performance of the boiling of DI water on a nanocoated surface was examined. The results showed that CHF and BHTC increase in comparison with the boiling of DI water on a bare heater.